2007
DOI: 10.1021/jp068639y
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Chirality for a Weakly Bound Adsorbate:  (R,R)- and (S,S)-Tartaric Acid/Ag(111)

Abstract: The interaction of tartaric acid (C4H6O6), including both (R,R) and (S,S) enantiomers, with Ag(111) has been studied using low-energy electron diffraction (LEED) and low-temperature scanning tunneling microscopy (STM). As evidenced by both diffraction and microscopy, this molecule binds very weakly to the Ag lattice, and the interadsorbate forces strongly dictate the formation of ordered monolayers that are globally chiral. In addition to a discussion of the role that hydrogen bonding plays in the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…perimental study on the persistence of chirality for the intact biacid molecules of ͑R,R͒and ͑S,S͒-tartaric acids on Ag͑111͒ has also been reported. 20 Although the chemical transformations of ͑R,R͒-tartaric acid on a metal surface are expected to correlate closely with enantioselectivity in the hydrogenation of ␤-ketoesters, [8][9][10] to our knowledge, the mechanisms of these chemical transformations have not been previously studied from theoretical calculations. In this paper, we carry out first principles slab calculations to systematically investigate, for the first time, the mechanisms for the chemical transformations of ͑R,R͒tartaric acid on a model Cu͑110͒ surface.…”
Section: Introductionmentioning
confidence: 99%
“…perimental study on the persistence of chirality for the intact biacid molecules of ͑R,R͒and ͑S,S͒-tartaric acids on Ag͑111͒ has also been reported. 20 Although the chemical transformations of ͑R,R͒-tartaric acid on a metal surface are expected to correlate closely with enantioselectivity in the hydrogenation of ␤-ketoesters, [8][9][10] to our knowledge, the mechanisms of these chemical transformations have not been previously studied from theoretical calculations. In this paper, we carry out first principles slab calculations to systematically investigate, for the first time, the mechanisms for the chemical transformations of ͑R,R͒tartaric acid on a model Cu͑110͒ surface.…”
Section: Introductionmentioning
confidence: 99%
“…Previous LEED and room temperature STM results showed that enantiopure films of tartaric acid are weakly bound to the Ag(111) substrate. 26 Room temperature STM studies for the racemic films confirm the same behavior, namely mobile domains whose perimeters are easily perturbed by repeated scanning of the STM tip. Therefore, in an effort to elucidate the molecular-level structure in the absence of thermally induced motion, the dual-component tartaric acid monolayers were imaged at cryogenic temperatures.…”
Section: Resultsmentioning
confidence: 66%
“…The relative chirality of the (S,S)-and (R,R)-tartaric acid domains is evidenced by structural modulation bands that arise for the enantiopure films. 26 These features, whose directionality are enantiomer dependent and, therefore, are a signature of a specific chiral arrangement for this system, are the result of a mismatch between the tartaric acid and the Ag(111) lattice and the spacings between the bands are sensitive to the local molecular density. The bright area between the two enantiopure domains is most likely the result of domain growth overlap, but the presence of separate chiral domains indicates that the formation of a single tartaric acid layer is preferred to direct multilayer growth.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations